2014
DOI: 10.1007/s12291-014-0448-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Imprecision, Bias and Total Error of Clinical Chemistry Analysers

Abstract: Context Two Biosystems analysers are used in our laboratory, a fully automated A25 and a semi-automated BTS-350. Internal quality control is done for both but external quality control only for A25. As BTS-350 is used for backup, it is important that the results of both analysers are not just comparable but also within predefined limits of systematic, random and total error (TE). Aim To evaluate the imprecision, bias and TE of the two Biosystem analysers. Materials and Methods Biosystems level-1 quality control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…Other study 6 but on two different analyzers showed Creatinine assay's (method not specified) TAE of 7.9 and 9.6 respectively. Another study 7 with pooled frozen serum of higher than normal creatinine levels showed error within minimal specifications.…”
Section: Resultsmentioning
confidence: 92%
“…Other study 6 but on two different analyzers showed Creatinine assay's (method not specified) TAE of 7.9 and 9.6 respectively. Another study 7 with pooled frozen serum of higher than normal creatinine levels showed error within minimal specifications.…”
Section: Resultsmentioning
confidence: 92%
“…This "multi-source" data set consists of 150 remaining entries. Except slightly less populated margin areas, the histogram of the multi-source data is similar to the full-data histogram (compared in [16] [18,19] were derived from biological variations (see [20,21]). The 95% confidence intervals of λ based on the multi-source dataset are 2.23±0.5 (for κ=2.33) and 2.0±0.4 (for κ=1.96).…”
Section: The Relation Between Optimal Limits For Smc and Ramentioning
confidence: 99%
“…For example, the limits given in the German guideline (Rili-BAEK, table B1a-c column 3, in relative values [15]) can be considered as sole LSMC data [16]. In contrast to the determination of LΔ, the definition of LSMC is usually done empirically at a certain significance level and/or related to a fraction of the biological variation of the analyte [20,21]. The determination of LSMC might also base on Eq.…”
Section: Smart Utilizing the Limit Dedicated For Single Measures (Lsmc)mentioning
confidence: 99%
“…In addition, all entries by Ricos, which base on more than one reference source, are again analyzed separately, due to the assumption that these entries represent well-studied techniques to a greater extent. Biases and imprecisions by Ricos et al are derived from biological variations of each analyte (see [9,10]). Thus, they usually represent higher limits compared to the state-of-the-art limits of uncertainty.…”
Section: Common Vs Different Limits For Smc and Ramentioning
confidence: 99%
“…With regard to the entire spectrum of analytes in Ricos et al and a large decision flexibility in κ (1.65-2.33), λ would have a maximum uncertainty of 2.00 ± 0.45. This extended uncertainty, mainly originating from differences in biological variation [9,10], would be too liberal for limits based on state-of-the-art.…”
Section: Common Vs Different Limits For Smc and Ramentioning
confidence: 99%